2019
DOI: 10.1111/neup.12592
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2/Bax ratio increase does not prevent apoptosis of glia and granular neurons in patients with temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is usually associated with hippocampal sclerosis (HS), characterized by gliosis and neuronal loss, mainly in the cornus ammonis (CA). Regardless the type of HS, gliosis is associated with neuronal loss. Indeed, glial reactivation seems to induce both neuronal and glial apoptosis. Anti‐apoptotic mechanisms are also activated in order to contain the cell death in chronic epilepsy. However, the role of the intrinsic apoptosis pathway in human TLE is unclear, mainly in relation to glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, the activation of STAT1 was previously found to be involved in the regulation of apoptosis by regulating the downstream Bcl-2 family members, Bcl-2 and Bax ( 24 ). The ratio between the anti-apoptotic protein Bcl-2 and the proapoptotic protein Bax has been revealed to be inversely correlated with the rate of apoptosis ( 25 , 26 ). Caspase-3 is an apoptosis-executing protein in the caspase family and functional cleaved caspase-3 is known to promote apoptosis together with Bcl-2 ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the activation of STAT1 was previously found to be involved in the regulation of apoptosis by regulating the downstream Bcl-2 family members, Bcl-2 and Bax ( 24 ). The ratio between the anti-apoptotic protein Bcl-2 and the proapoptotic protein Bax has been revealed to be inversely correlated with the rate of apoptosis ( 25 , 26 ). Caspase-3 is an apoptosis-executing protein in the caspase family and functional cleaved caspase-3 is known to promote apoptosis together with Bcl-2 ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, which is localized primarily in the cytoplasm, exerts its anti-apoptotic effect via targeting to the nucleus. Conversely, Bax, another crucial mediator, diminishes the anti-apoptotic effect of Bcl-2, ultimately leading to apoptotic cell death [ 29 ]. Our examination of Bax and Bcl-2 expression in CHON-001 cells revealed that IL-1β stimulation amplified BAX expression while concurrently inhibiting BCL-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports that both BAX and Bcl-X L genes/proteins are expressed in the neocortical region of temporal lobe epilepsy ( Henshall et al, 2000 ). Beside, an aberrant expression pattern of BAX and Bcl-X L has been reported to participate in several other neurological disorders including epilepsy with focal cortical dysplasia and hippocampal sclerosis ( McMasters et al, 2000 ; Chamberlain and Prayson, 2008 ; Toscano et al, 2019 ). In focal cortical dysplasia type IIb, balloon cells a histopathological characteristic, have shown apoptotic protein expression in the epileptic tissue regions, with 61% of cases in this study showing >50% of balloon cells expressing BAX ( Chamberlain and Prayson, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple alternative apoptotic signaling pathways also may participate ( Henshall and Simon, 2005 ), beyond pro-apoptotic and anti-apoptotic ratio in epilepsy due to ASM interactions. Another report showed that despite an increase in the Bcl-2/BAX ratio, the granular neurons and glia exhibited active caspase-3 expression in temporal lobe epilepsy hippocampi compared to controls ( Toscano et al, 2019 ), where glial and neuronal death were found to be increased in sclerotic hippocampi, independently of hippocampal type pathology and co-localization found with gliosis. Furthermore, in the current study among the patient cohort, the patients that received ASMs as NON-CYP + CYP substrates or inducers in combination showed relatively balanced redox homeostasis with increased level of reduced glutathione and lower lipid peroxidation levels, together indicating an altered dynamic in apoptotic and mitochondrial proteins levels (schematic representation in Figure 2C ).…”
Section: Discussionmentioning
confidence: 99%